2007
DOI: 10.1074/jbc.m704875200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Structural Changes in a G Protein-coupled Receptor Caused by Different Classes of Agonist Ligands

Abstract: The activity of G protein-coupled receptors can be modulated by different classes of ligands, including agonists that promote receptor signaling and inverse agonists that reduce basal receptor activity. The conformational changes in receptor structure induced by different agonist ligands are not well understood at present. In this study, we employed an in situ disulfide crosslinking strategy to monitor ligand-induced conformational changes in a series of cysteine-substituted mutant M 3 muscarinic acetylcholine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 49 publications
4
81
0
Order By: Relevance
“…Heparinbinding motifs were described in proteins with sequences such as XBBBXXBX and XBBXBX (where B and X are basic and hydropathic residues, respectively). 42 M 3 receptors do not have heparin-binding sites on the extracellular loops, 43 which is in accordance with the absence of heparin binding to muscarinic receptors ( Figure 4C and 4D). In addition, other possibilities to explain heparin-induced relaxation were evaluated.…”
Section: Discussionsupporting
confidence: 62%
“…Heparinbinding motifs were described in proteins with sequences such as XBBBXXBX and XBBXBX (where B and X are basic and hydropathic residues, respectively). 42 M 3 receptors do not have heparin-binding sites on the extracellular loops, 43 which is in accordance with the absence of heparin binding to muscarinic receptors ( Figure 4C and 4D). In addition, other possibilities to explain heparin-induced relaxation were evaluated.…”
Section: Discussionsupporting
confidence: 62%
“…Allosteric ligands are defined by the fact that in the absence of an orthosteric ligand, they do not affect the activity of a receptor (7) but that they alter the affinities of orthosteric ligands, presumably because of conformational changes in the receptor (8 -10). Recent experimental evidence supports the hypothesis that allosteric ligands can induce specific receptor conformations by direct binding to an allosteric ligand site and that this may result in changes of the agonist-induced activity of the receptor (11).…”
mentioning
confidence: 83%
“…That agonist binding induces a conformational change involving H8 was suggested by a cysteine substitution and induced disulfide cross-linking study on the M 3 mAChR (Li et al, 2007). Increased spatial separation or conformational mobility between the N-terminal segment of H8 and TM1 is a favored interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…H8, in particular, a dileucine motif toward the C-terminal end, also has been implicated in control of receptor expression (Sawyer et al, 2010) and is suggested to be part of a dimerization interface involving TM1 (Fung et al, 2009). In the M 3 mAChR, cysteine substitution and disulfide cross-linking studies indicated that the N-terminal part of H8 moves away from TM1 during agonist activation (Li et al, 2007) and that residues in H8 can undergo both agonistindependent and -dependent cross-linking to G q ␣ (Hu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%